Opposing role of condensin hinge against replication protein A in mitosis and interphase through promoting DNA annealing. Issue 4 (December 2011) - Akai, Yuko; Kurokawa, Yumiko; Nakazawa, Norihiko; Tonami-Murakami, Yuko; Suzuki, Yuki; Yoshimura, Shige H.; Iwasaki, Hiroshi; Shiroiwa, Yoshiharu; Nakamura, Takahiro; Shibata, Eri; Yanagida, Mitsuhiro
Abstract : Condensin is required for chromosome dynamics and diverse DNA metabolism. How condensin works, however, is not well understood. Condensin contains two structural maintenance of chromosomes (SMC) subunits with the terminal globular domains connected to coiled-coil that is interrupted by the central hinge. Heterotrimeric non-SMC subunits regulate SMC. We identified a novel fission yeast SMC hinge mutant, cut14-Y1, which displayed defects in DNA damage repair and chromosome segregation. It contains an amino acid substitution at a conserved hinge residue of Cut14/SMC2, resulting in diminished DNA binding and annealing. A replication protein A mutant, ssb1-418, greatly alleviated the repair and mitotic defects of cut14-Y1 . Ssb1 protein formed nucleolar foci in cut14-Y1 cells, but the number of foci was diminished in cut14-Y1 ssb1-418 double mutants. Consistent with the above results, Ssb1 protein bound to single-strand DNA was removed by condensin or the SMC dimer through DNA reannealing in vitro . Similarly, RNA hybridized to DNA may be removed by the SMC dimer. Thus, condensin may wind up DNA strands to unload chromosomal components after DNA repair and prior to mitosis. We show that 16 suppressor mutations of cut14-Y1 were all mapped within the hinge domain, which surrounded the original L543 mutation site.